Doctors and Medical Practices in Ann Radcliffe’s The Romance of the Forest - Serena Baiesi (Lea)
Medical practice and the Gothic imagination within the context of medicine and literature in the late eighteenth century present fruitful intersections that have only recently been investigated, since they both transgress and test the limits of human knowledge. As a major representative of Gothic fiction, Ann Radcliffe frequently includes surgeons and physicians in her romances, who experiment with several methods of alleviating and curing mental as well as bodily diseases. Even though their marginal role in Radcliffe’s works is often overlooked by critical studies, this article offers a new and original enquiry on the dynamics of injuries, the methods of cure and the relationship between patients and doctors that Radcliffe employs in The Romance of the Forest (1791) in order to challenge traditional interpretations of Gothic medical issues as well as gender roles.